Covid-19 and Border Restriction Policies: The Dilemma of Trans-Border Truck Drivers in East Africa - Calvince Omondi Barack; Gerishon Barack Munga (Goodwood Publishing, 2021)
Purpose: The study aims to critically assess the challenges that were faced by trans-border truck drivers within the East African Community (EAC) as a result of the Covid-19 pandemic and its management protocols. Research Methodology: While adopting the qualitative research method, this paper has used documents including documented interviews and virtual sources for its data. The data have been analyzed using qualitative content analysis through which themes have been generated for discussions. Results: The EAC member countries should continue to harmonize their health standardization to enable them to enjoy the pursuit and use of OSBP even during pandemics. Conclusions: The EAC member countries need to harmonize health standards and establish a joint data-sharing platform to improve cross-border management and coordination during emergencies. Limitations: This paper is limited to the long-distance truck drivers and the management of Covid-19 within the East African Community and does not cover other aspects of Coordinated Border Management in the region. Contributions: It contributes to harmonizing and standardizing community operations and health measures to address coordinated border management challenges and future single market readiness. Novelty: This study provides a unique perspective on the impact of COVID-19 border restrictions by focusing on the experiences of trans-border truck drivers in East Africa, an often-overlooked group in cross-border trade studies.